2022
DOI: 10.7759/cureus.21826
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Late Diagnosis of Latent Autoimmune Diabetes in Adults

Abstract: Latent autoimmune diabetes of adults (LADA) is a type of autoimmune diabetes that begins in adulthood (usually after the age of 35 years); its main feature is the presence of diabetes-associated autoantibodies (most often autoantibody against glutamic acid decarboxylase), which leads to progressive destruction of the islets of Langerhans. This is a heterogeneous condition that presents with clinical and laboratory manifestations common to type 1 diabetes and type 2 diabetes.We report a case of a 71-year-old ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…According to a study, patients of LADA showed lower triglycerides and higher HDL cholesterol level as compared to Type 2 Diabetes mellitus. 11 Lastly, DIC seen in this case can be attributed to the previous history of multiple blood transfusions done in the last 1 year. Recognizing Zieve's syndrome promptly is crucial to prevent unwarranted and potentially detrimental interventions.…”
Section: Discussionmentioning
confidence: 69%
“…According to a study, patients of LADA showed lower triglycerides and higher HDL cholesterol level as compared to Type 2 Diabetes mellitus. 11 Lastly, DIC seen in this case can be attributed to the previous history of multiple blood transfusions done in the last 1 year. Recognizing Zieve's syndrome promptly is crucial to prevent unwarranted and potentially detrimental interventions.…”
Section: Discussionmentioning
confidence: 69%
“…According to studies, despite the fact that they resemble type 1 diabetes patients in this regard, it was found that LADA patients have greater C peptide levels than individuals with adult-onset type 1 diabetes even after 10 years of diabetes. These patients also required insulin therapy earlier as compared to that of Type 2 diabetes patients ([ 8 , 9 , 11 , 12 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The table below shows the major key points and comparison between Type 1, Type 2 DM, LADA and our case [ 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%